2015
DOI: 10.1186/s40249-015-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the basic reproductive ratio for the Ebola outbreak in Liberia and Sierra Leone

Abstract: BackgroundEbola virus disease has reemerged as a major public health crisis in Africa, with isolated cases also observed globally, during the current outbreak.MethodsTo estimate the basic reproductive ratio R0, which is a measure of the severity of the outbreak, we developed a SEIR (susceptible-exposed-infected-recovered) type deterministic model, and used data from the Centers for Disease Control and Prevention (CDC), for the Ebola outbreak in Liberia and Sierra Leone. Two different data sets are available: o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 19 publications
4
68
1
3
Order By: Relevance
“…Furthermore, for the given parameter value in Table 3, the value of R 0 for the 2014 Ebola outbreak in Sierra Leone is R 0 = 1.64277. Although this estimate is lower than that reported by Althaus 11 and slightly greater than Khan et al, 32 it fits well with the recent outbreak scenario in Sierra Leone.…”
Section: In the Absence Of Diffusionsupporting
confidence: 86%
“…Furthermore, for the given parameter value in Table 3, the value of R 0 for the 2014 Ebola outbreak in Sierra Leone is R 0 = 1.64277. Although this estimate is lower than that reported by Althaus 11 and slightly greater than Khan et al, 32 it fits well with the recent outbreak scenario in Sierra Leone.…”
Section: In the Absence Of Diffusionsupporting
confidence: 86%
“…The growing concern over the repeated emergence of EVD (7,8) has stimulated many studies on these outbreaks, in particular on the most recent one in West Africa, trying to understand the transmission mechanisms and the effectiveness of containment strategies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These studies, however, either used limited data at an early stage of the epidemic or assessed a single influential factor.…”
mentioning
confidence: 99%
“…At national level, our approach was not comparable to results of other methods. Several mechanistic [6,10,14,[16][17][18][19][50][51][52] and phenomenological [15,34,53] The ecological analysis showed associations between R 0 and population-level factors linked to urbanisation and crowding. Analysis at the population-level is appropriate when the mechanism of action involves interactions between individuals, for example the potential for spread of an infection in densely populated areas [54].…”
Section: Discussionmentioning
confidence: 99%
“…A common approach to the estimation of R 0 consists of fitting mathematical transmission models to observed outbreak data. In the West African EVD epidemic, several mathematical modelling studies have described the variation in R 0 between [6,10,[14][15][16][17][18][19] and within [20][21][22][23][24][25] the three countries. Most studies found estimates of R 0 ranging between 1.5 and 2.5, agreeing with results from models of earlier outbreaks ranging from 1.4-4.7 (summarised in [26]).…”
Section: Introductionmentioning
confidence: 99%